Graduate students would benefit from guidelines for preparing conference abstracts: A rhetorical moves analysis of French-language conference abstracts in language-related fields - Frazer-McKee, Gabriel; Vogh, Kendall (Working papers in Applied Linguistics and Linguistics at York, 2022)
Graduate student writing is finally receiving substantial scholarly attention, but little is known about the characteristics of the unstructured graduate student conference abstract (GSCA). This study seeks to characterize the rhetorical structures of GSCAs, as a basis for identifying potential writing support strategies. 107 French-language GSCAs from language-related fields (e.g., linguistics, second-language teaching) were coded using Hyland’s rhetorical moves (RMs) (Background-Aims-Methods-Results-Conclusion), yielding measures for RM frequency, RM sequencing, and RM recycling. We then use these measures to identify GSCAs that pattern together, via K-Means clustering. We find that the GSCAs studied pattern into three subtypes, two of which (72%) exhibit informational and/or structural shortcomings, most notably (1) missing RMs, (2) cognitively difficult RM sequences, and (3) unbalanced word-to-RM allotment. This study thus confirms that there is a need to implement strategies (e.g., conference submission guidelines) to better support graduate students in mastering this academic genre’s normative content and structure.